The Meaning and Significance of the Old Assyrian sikkātum - Brinker, Christopher (Altorientalische Forschungen, 2010)
This article reviews the published corpus of Old Assyrian letters containing the noun sikkātum . Here it is argued that the sikkātum was not a religious procession, but instead that it was an extramural marketplace. Trade at this marketplace involved a high volume of metals and probably operated only seasonally, relating to the arrival of the earliest caravans in Anatolia. Furthermore, it is suggested that sikkātum is related to the west semtic word sukhōt and was used to refer to this seasonal extramural metals marketplace by metonymy.